Model test on the effects of some root properties on pullout capacity / Siti Sara Seera Mustapa Kamil - Siti Sara Seera , Mustapa Kamil (2013)
The study is aimed to investigate the morphology functional of plant root systems in relation to their roles in providing anchorage and stability to the plant. Since the adoption of bioengineering technique in solving numerous geotechnical failures has rapidly increased these days, this research can be beneficial in providing additional knowledge towards a greater insight of soil-root mechanical interactions. The anchorage of different types of root systems was investigated together with the influences of several mechanical factors on their development. The roles of root branching patterns and root tapering behaviour as well as root material stiffness to the anchorage and stability of plant have been selected as the mechanical factors to be studied. The research was conducted and completed by carrying out a series of laboratory pullout test using physical models. Throughout this study, pullout resistances of the artificial root models were measured by subjecting the various patterns of the physical root models to the vertical uprooting forces using a laboratory pullout machine. The laboratory tests were chosen to conduct quick experiments on the root pullout strength. By doing so, the identical soil samples could be prepared while various and common simple root patterns could be developed and studied in great details. Model experiments were successfully verified as well as confirming the theoretical predictions that demonstrate the importance of root branching pattern in the stability of plant through root anchorage controlled by the number of lateral root, angle and position of the lateral root to the taproot and the total length of taproot in a root system. A second model study on a series of tapered root models has also revealed the behaviour of root tapering in weakening the anchorage of soil-root composites due to the response of confining pressure by the soil medium that acted on the components of root model during pullout. The confining pressure was higher at the root tip compared to the other points of the upper root length to the lateral branching point as a consequence of force concentration at a smaller area of root tip. This caused the point to bend easily and quickly that led into less resistance of the tapered root models to pullout. While investigating on the influences of root material stiffness as one of the major sources of soil-root anchorage to the stability of plants, the aluminum root models were identified to be more difficult to uproot in contrast to the flexible root material made out of high density polyethylene (HDPE) material. As the high density polyethylene (HDPE) material represents the flexible root models, the pullout resistances generated were less than those produced by the uniform aluminum root models which represent the harder and stiffer root models. In a conclusion, root morphologies and the highlighted mechanical factors studied have impressively proven in being such a significant influence on the root anchorage of plants and this knowledge can be considered beneficial if vegetation is to be practiced extensively.